Application of a modified graphite paste electrode to the detection of fluorene in fuscous latices. Issue 1 (1st October 2022) - Liu, Yu; Luo, Qi; Tian, Qiping; Xu, Wen; Hu, Huili; Shi, Li
Abstract: A graphite paste electrode (GPE) was obtained by immobilizing graphene, and the electrocatalytic activity of fluorene (Flu) was studied. The voltammetric behavior using graphene-modified GPE showed an irreversible redox reaction for Flu-ACN-KClO4 . A good linear correlation between anodic I and C Flu ranged within 8–300 ng mL −1 . Therefore, we recommend a facile synthesis of modified GPE impregnated with Flu, which matched the concept of analytical minimalism. The electrochemical detection method combined with portable potentiostat is promising to be used for the field tests of Flu in fuscous latices as well as other polycyclic aromatic hydrocarbons.